Nonlinear modeling of structures with bolted joints: a comparison of two approaches based on a time-domain and frequency-domain solver - Lacayo,R; Pesaresi,L; Gross,J; Fochler,D; Armand,J; Salles,L; Schwingshackl,C; Allen,M; Brake,M (Mechanical Systems and Signal Processing, 2019)
Motivated by the current demands in high-performance structural analysis, and by a need to better model systems with localized nonlinearities, analysts have developed a number of different approaches for modeling and simulating the dynamics of a bolted-joint structure. However, it is still unclear which approach might be most effective for a given system or set of conditions. To better grasp their similarities and differences, this paper presents a numerical benchmark that assesses how well two diametrically differing joint modeling approaches – a time-domain whole-joint approach and a frequency-domain node-to-node approach – predict and simulate a mechanical joint. These approaches were applied to model the Brake-Reuß beam, a prismatic structure comprised of two beams with a bolted joint interface. The two approaches were validated first by updating the models to reproduce the nonlinear response for the first bending mode of an experimental Brake-Reuß beam. Afterwards, the tuned models were evaluated on their ability to predict the nonlinearity in the dynamic response for the second and third bending modes. The results show that the two joint modeling approaches perform about equally as well in simulating the Brake-Reuß beam. In addition, the exposition highlights improvements that were made in each method during the course of this work and reveal further challenges in advancing the state-of-the-art.